'Switch to love, switch to kill—dose and light co-regulate iron single-atom nanozyme to modulate cell fate. (10th December 2022) - Zhe, Yadong; Liu, Jia; Zhao, Zhiqiang; Li, Zaoming; Li, Kai; Lin, Yuqing
Abstract: Remote control of cells and the regulation of cell events at the molecular level are of great interest to the biomedical field. In addition to mechanical forces and genes, chemical compounds and light play pivotal roles in regulating cell fate, which have boosted the fast growth of biology. Herein, we synthesized light-regulated, atomically dispersed Fe-N4 immobilized on a carbon substrate nanozyme (Fe-N/C single atom catalysts), whose peroxidase- and catalase-like properties can be enhanced by 120% and 135%, respectively, under 808-nm laser irradiation through the photothermal effect of Fe-N/C. Interestingly, a switch to love/switch to kill interaction between Fe-N/C dose and near-infrared (NIR) light co-regulating the Fe-N/C nanozyme to modulate cell fate was discovered. Based on this, we found that under NIR light irradiation, when the dose of Fe-N/C is low, it can scavenge more reactive oxygen species (ROS) and achieve cell protection; when the dose of Fe-N/C is too high, it tended to lead to cell apoptosis. This work not only provides an effective strategy for the regulation of nanozyme activity but also realizes the dual-functional application of nanozyme materials for the treatment of some specific diseases.